Cutaneous mastocytosis: Two pediatric cases treated with topical pimecrolimus. - Correia, O (2014)
Cutaneous mastocytosis is characterized by increased numbers of skin mast cells that release mediators causing pruritus, urticaria, and flushing. Most pediatric mastocytosis patients exhibit the pattern of urticaria pigmentosa, which typically appears during the first two years of life and resolves spontaneously in late adolescence. However, while the disease is active, patients are frequently symptomatic and uncomfortable, which justifies symptomatic treatment. We report 2 patients, a 14-month-old girl and a 26-month-old boy, with localized cutaneous erythematous lesions with a positive Darier sign. In each, a punch biopsy confirmed the diagnosis of mastocytosis. Treatment was instituted with pimecrolimus cream twice a day and oral antihistamine. An almost complete response was achieved after 4 months of therapy in both patients, with no clinical evidence of recurrence after 4 years and 2 years of follow-up, respectively. In children, the treatment of mastocytosis is directed primarily to avoiding potential mast cell degranulating agents and alleviating symptoms. Topical calcineurin inhibitors act by inhibiting T-cell activation and cytokine release; they may suppress mast cell- mediated reactions by reducing their degranulation. These two cases suggest that in localized cutaneous mastocytosis they are a safe and efficacious alternative to topical steroid therapy.